Teacher experience and the class size effect - experimental evidence - Steffen Mueller (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2011)
We analyze teacher experience as a moderating factor for the effect of class size reduction on student achievement in the early grades using data from the Tennessee STAR experiment with random assignment of teachers and students to classes of different size. The analysis is motivated by the high costs of class size reductions and the need to identify the circumstances under which this investment is most rewarding. We find a class size effect only for senior teachers. The effect is most pronounced for higher and average-performing students. We further show that senior teachers outperform rookies only in small classes. The results have straightforward policy implications. Interestingly, the class size effect is most likely due to a higher quality of instruction in small classes and not due to less disruptions.
Keywords: I2; H4; J4; 330; class size reduction; teacher experience; student achievement